2021
DOI: 10.1186/s13068-021-01914-0
|View full text |Cite
|
Sign up to set email alerts
|

cAMP activates calcium signalling via phospholipase C to regulate cellulase production in the filamentous fungus Trichoderma reesei

Abstract: Background The filamentous fungus Trichoderma reesei is one of the best producers of cellulase and has been widely studied for the production of cellulosic ethanol and bio-based products. We previously reported that Mn2+ and N,N-dimethylformamide (DMF) can stimulate cellulase overexpression via Ca2+ bursts and calcium signalling in T. reesei under cellulase-inducing conditions. To further understand the regulatory networks involved in cellulase overexpression in T. reesei, we characterised the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…We showed that Ca 2+ was accumulated inside fungal cells upon plasma treatment. In Trichoderma reesei , Ca 2+ promotes the transcription of cellulase genes such as cbh1 and cbh2 by activating the calmodulin-Crz1 signaling pathway [ 10 , 37 , 38 ]. Nevertheless, it is not clear whether the increase in Ca 2+ levels within cells affected the expression of cellulolytic enzyme genes because we measured the Ca 2+ level 48 h after the plasma treatment, which was far beyond the gene expression time window.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that Ca 2+ was accumulated inside fungal cells upon plasma treatment. In Trichoderma reesei , Ca 2+ promotes the transcription of cellulase genes such as cbh1 and cbh2 by activating the calmodulin-Crz1 signaling pathway [ 10 , 37 , 38 ]. Nevertheless, it is not clear whether the increase in Ca 2+ levels within cells affected the expression of cellulolytic enzyme genes because we measured the Ca 2+ level 48 h after the plasma treatment, which was far beyond the gene expression time window.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge on the regulatory molecular mechanism of cellulase synthesis in filamentous fungi is prerequisite for rationally engineering fungal strains to improve the production of cellulase and other proteins, such as pharmaceutical proteins and industrial enzymes, which has received increasing attention [ 15 ]. It has been reported that cellulase production is regulated by varied signal pathways, such as carbon catabolite repression (CCR) [ 16 ], calcium signal transduction pathway [ 17 ], and the TOR pathway [ 18 ]. When glucose exists, CCR is induced through the transcription factor CRE1 to almost completely block the cellulase production [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…When glucose exists, CCR is induced through the transcription factor CRE1 to almost completely block the cellulase production [ 16 ]. In contrast, the Ca 2+ burst through calcium signal transduction pathway can strengthen the cellulase production and cell metabolism [ 17 ]. However, whether IR and NMD is involved in cellulase biosynthesis in filamentous fungi and how, remain totally unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge on the regulatory molecular mechanism of cellulase synthesis in lamentous fungi is prerequisite for rationally engineering fungal strains to improve the production of cellulase and other proteins like pharmaceutical proteins and industrial enzymes, which has received increasing attention [15]. It has been reported that cellulase production is regulated by varied signal pathways, like carbon catabolite repression (CCR) [16], calcium signal transduction pathway [17], and the TOR pathway [18]. When glucose exists, CCR is induced through the transcription factor CRE1 to almost completely block the cellulase production [16].…”
Section: Introductionmentioning
confidence: 99%
“…When glucose exists, CCR is induced through the transcription factor CRE1 to almost completely block the cellulase production [16]. In contrast, the Ca 2+ burst through calcium signal transduction pathway can strengthen the cellulase production and cell metabolism [17]. However, whether IR and NMD is involved in cellulase biosynthesis in lamentous fungi and how, remain totally unknown.…”
Section: Introductionmentioning
confidence: 99%